If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -3 + x = 6 Reorder the terms: -3 + X + x = 6 Solving -3 + X + x = 6 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '3' to each side of the equation. -3 + X + 3 + x = 6 + 3 Reorder the terms: -3 + 3 + X + x = 6 + 3 Combine like terms: -3 + 3 = 0 0 + X + x = 6 + 3 X + x = 6 + 3 Combine like terms: 6 + 3 = 9 X + x = 9 Add '-1x' to each side of the equation. X + x + -1x = 9 + -1x Combine like terms: x + -1x = 0 X + 0 = 9 + -1x X = 9 + -1x Simplifying X = 9 + -1x
| -6z-9+2z=18 | | 5x^3-60x^2-175x=0 | | 8=y-1 | | -19=3+8(d-5) | | -4x+2=-18 | | -6(1+9c)=20 | | 22,000-16,000/12x | | 5z-9/-6=17 | | logy=3.4 | | X-3-x=6 | | -17+9a=7(4a-8) | | 6z-1/4=5/4 | | -7x-1=13 | | 28/8=7/x | | 24=-6(8v+3) | | (a^2-10a+16)/(a-2) | | -19x-34=56x | | 4/(41/3) | | 9(2x-6)=-27 | | 2/6=4/x | | 9x-8=7x^2 | | 9x+2(3x-1)=15x-2 | | 5/3*3 | | 3(6b-5)=-25+7b | | 4+9-4*1+8*2-5*2= | | logy=1.2 | | (x^2-5x-6)/(x-6) | | -100/1x+60=25 | | 4k+9k=-35 | | 1=4x+3*5/3-2/3x | | 2u^(-3/2)=1/5 | | x/2x=-8 |